English-based feminative neologisms in post-1989 Polish - Agnieszka Małocha (Beiträge zur Allgemeinen und Vergleichenden Sprachwissenschaft)
For more than three decades now an increase in the productivity of the feminative category has been observed in Polish-language communication practices and, consequently, an increase in the number of female personal names in Polish. The lexicographic team of the Formation of Feminine Names Research Unit, operating at the Institute of Polish Studies at the University of Wrocław since 2010, has been registering those changes and is currently working on a new edition of the “Dictionary of Polish Feminine Nouns”. Its corpus includes, among others, about 150 of the newest feminine lexemes created after 1989 and based on English roots. The article presents their lexico-semantic typology and juxtaposes it with earlier typologies of feminine names, thus showing which areas of activity of contemporary women are filled with innovative nominalizations. It also proves the compatibility with the Polish language system of the analysed hybrid feminine names, which, despite showing a varying degree of orthographic, phonetic and morphological adaptation, are generally accepted by young people, as attested to by a survey conducted among students of Polish Studies at the University of Wrocław. The discussion on internationalization of feminine forms – one of the ways of filling the semantic and lexical gaps in the naming of women – is set against the background of the political, cultural and communicative changes which have taken place in the Third Republic of Poland.